Talented but disruptive: An exploration of problematic players in sports teams - Leggat, F. J.; Smith, M. J.; Figgins, S. G. (Journal of Applied Sport Psychology, 2020)
This study aimed to enhance the understanding of problematic players, who have been identified as highly talented but negative influences in team sport. Using semi-structured interviews, 15 players and coaches` experiences of problematic players were explored. Results were divided into features, causes of behavior, impacts, and managerial considerations surrounding problematic players. Findings revealed problematic players share characteristics with narcissists. From an applied perspective, the negative impacts from these players are recognized, such as negative role modeling and lower team morale. Managerial considerations for these players are discussed, which could be beneficial for coaches working with problematic players and their negativity.